Corrosion behaviour of AA 1370 strands for wires: Identification of the critical metallurgical parameters. (15th April 2018) - Gravina, Rosanne; Josse, Claudie; Viguier, Bernard; Laurino, Adrien; Alexis, Joël; Hughes, Anthony E.; Blanc, Christine
Graphical abstract: Highlights: The forming process significantly influences the corrosion resistance. Ultra-fine grain structure is associated with low corrosion resistance of AA1370. The corrosion resistance depends on the density and misorientation of the interfaces. High angle grain boundaries are more reactive than low angle grain boundaries. Abstract: The corrosion behaviour of AA 1370 in different metallurgical states was studied in chloride-containing sulphate solutions. The microstructures of a rod, a deformed strand and an annealed strand constitutive of wires were examined using scanning electron microscopy, transmission electron microscopy and electron backscattered diffraction. Results offered evidence for the ultra-fine grain size, high density of interfaces and high level of misorientation of the interfaces as relevant explanations for the low corrosion resistance of the deformed strand compared to the rod and the annealed strand.